2016
DOI: 10.17221/351/2014-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warm and cold stratification, and ethanol treatment on germination of Corylopsis seeds

Abstract: Seed germination experiments with Corylopsis coreana, C. sinensis var. calvescens, and Corylopsis gotoana were conducted. Corylopsis coreana seeds were treated at 5, 7.5, 10, 12.5 and 20°C to study the upper temperature limit to break dormancy. Seeds of C. sinensis var. calvescens were treated 1 month with warm stratification (WS) at 10, 15, 20, and 25°C followed by cold stratification (CS) at 5°C for 0, 1, 2, and 3 months to understand the requirements of WS and CS to effectively break dormancy. Germination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Mature Corylopsis coreana seeds with fully developed endosperm and cotyledons sink when immersed in water, as verified by X-ray images (Kim et al, 2016), with germination percentages higher than 85 -90%. However, the presence of air space in mature dry seeds between the seed coat and endosperm or embryo may prevent seeds from sinking when immersed in water.…”
Section: Seed Maturity In Relation To Size Of Capsules X-ray Imagesmentioning
confidence: 69%
“…Mature Corylopsis coreana seeds with fully developed endosperm and cotyledons sink when immersed in water, as verified by X-ray images (Kim et al, 2016), with germination percentages higher than 85 -90%. However, the presence of air space in mature dry seeds between the seed coat and endosperm or embryo may prevent seeds from sinking when immersed in water.…”
Section: Seed Maturity In Relation To Size Of Capsules X-ray Imagesmentioning
confidence: 69%
“…Other evidence has suggested that ethanol may break dormancy by acting as a substrate for respiration thereby stimulating glycolysis (Adkins et al 1984b;Corbineau et al 1991). One recent study postulated that soaking seeds in an ethanol solution may alter the morphology of the seed coat, thus causing inhibitory chemicals such as abscisic acid to be leached from seeds, resulting in increased germination (Kim et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Miyoshi and Sato (1997) showed that concentrations of 1-5% ethanol over 10 days produced maximum germination of Oryza sativa L. Lycopersicon esculentum L. primed for 24 h with 2-4% ethanol improved germination (Afzal et al 2013). Higher concentrations of 25% ethanol for 15 min, or 25-75% ethanol for 10-120 min were used to overcome dormancy of Helianthus (Nasreen et al 2015) and Corylopsis (Kim et al 2016) species respectively.…”
Section: Introductionmentioning
confidence: 99%